Cultural chauvinism : intercultural communication and the politics of superiority - Ibelema, Minabere, 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the concept of cultural chauvinism as the sense of superiority that ethnic or national groups have of themselves relative to others, particularly in the context of international relations. Minabere Ibelema shows the various ways that academics, statesmen, and especially journalists, express their cultural groups' sense of superiority over others. The analysis pivots around the notion of "Western values" given its centrality in international relations and diplomacy. To the West, this stands for an array of largely positive political and civic values; to a significant portion of the global community, it embodies social pathos. Ibelema argues that often the most routine expressions go under the radar, even in this age of hypersensitivity. This book throws a unique light on global relations and will be of particular interest to scholars in international relations, communication studies and journalism studies"--
Many Faces of Cultural Chauvinism -- Democracy is Western -- All Things Modern Are Western -- All Things Nefarious Are Non-Western -- The Hell of War Is Non-Western -- All Things Decadent Are Western -- Immodest Dressers and Desecraters -- Contention Not Confucian -- As Democracies Turn -- Dark History of Distinctions -- Who Civilized the Greeks That Civilized the West? -- Convergence -- Onward From the Bridgehead -- Cultural Humility -- Postscript: An Oreo and Mozart.
OCLC-licensed vendor bibliographic record.
Keywords: Ethnocentrism; Chauvinism and jingoism; Culture; International relations; Intercultural communication; Civilization, Western; SOCIAL SCIENCE / Media Studies; LANGUAGE ARTS & DISCIPLINES / Journalism; POLITICAL SCIENCE / General